2020
DOI: 10.1002/mp.14300
|View full text |Cite|
|
Sign up to set email alerts
|

Preliminary clinical experience with Calypso anchored beacons for tumor tracking in lung SBRT

Abstract: Purpose: To present our preliminary experience with the recently released Calypso lung beacons to track lung tumor location during stereotactic body radiation therapy (SBRT). Materials/Methods: Five recent lung SBRT patients had Calypso lung beacons implanted for tumor tracking during treatment. Beacons were placed by a pulmonologist using fluoroscopic navigation within 1 week prior to planning four-dimensional computed tomography (4DCT) acquisition. Patients were immobilized in a full-body double-vacuum bag. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…39 One study used a verification CBCT acquired before treatment and compared the shifts determined from the CBCT and planning CT registration to the shifts reported by Calypso during the CBCT acquisition and found the differences to be ≤1.5 mm. 37 The same study also used the GR reported by the Calypso system at the time of setup as an indication of EMT stability throughout treatment. 38 McDonald et al evaluated the long-term stability of EMTs by registering follow-up CTs with the planning CT and found that the long-term stability was comparable to other commercially available lung fiducial markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 One study used a verification CBCT acquired before treatment and compared the shifts determined from the CBCT and planning CT registration to the shifts reported by Calypso during the CBCT acquisition and found the differences to be ≤1.5 mm. 37 The same study also used the GR reported by the Calypso system at the time of setup as an indication of EMT stability throughout treatment. 38 McDonald et al evaluated the long-term stability of EMTs by registering follow-up CTs with the planning CT and found that the long-term stability was comparable to other commercially available lung fiducial markers.…”
Section: Discussionmentioning
confidence: 99%
“…37 The same study also used the GR reported by the Calypso system at the time of setup as an indication of EMT stability throughout treatment. 38 McDonald et al evaluated the long-term stability of EMTs by registering follow-up CTs with the planning CT and found that the long-term stability was comparable to other commercially available lung fiducial markers. 36 Schmitt et al found that intra-and interfractional variations in EMT distances varied up to 3.2 mm for patients treated with free breathing.…”
Section: Discussionmentioning
confidence: 99%
“…27 One clinic has reported using implanted electromagnetic transponders similarly, as an added layer of safety during lung SBRT treatments. 7 When only one viewing angle is necessary and only one angle provide sufficient image quality for visualization, then verification images could be acquired from that angle alone. This would halve the required radiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…Fiducial markers are of considerable help in this 60 ‘Image guidance’ may not require an image. For example, implanted radio transponders that can be localised from outside can determine the location of a target, but do not provide an image 61,62 Training of staff is an essential part of image guidance, in particular for modalities such as ultrasound which may require experienced users 63 …”
Section: Treatment Delivery: Technology and Techniquesmentioning
confidence: 99%